1994
DOI: 10.1002/1097-0355(199424)15:4<348::aid-imhj2280150404>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Infants of “depressed” mothers interact better with their nondepressed fathers

Abstract: To determine whether infants of “depressed” mothers interact better with their nondepressed fathers, twenty‐six 3‐ to 6‐month‐old infants were videotaped during face‐to‐face interactions with their parents. The “depressed” mother group consisted of twelve 3‐ to 6‐month‐old infants and their “depressed” mothers and nondepressed fathers. The control group was composed of 14 nondepressed mothers and nondepressed fathers and their 3‐ to 6‐month‐old infants. In the “depressed” mother group, the nondepressed fathers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
1
11

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 20 publications
4
54
1
11
Order By: Relevance
“…This was a surprising finding inasmuch as depressed fathers versus depressed mothers have typically shown more positive interactions behaviors with their infants (Field, Hossain & Malphurs, et al, 1999;Hossain, Field, Gonzalez, Malphurs, DelValle & Pickens, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This was a surprising finding inasmuch as depressed fathers versus depressed mothers have typically shown more positive interactions behaviors with their infants (Field, Hossain & Malphurs, et al, 1999;Hossain, Field, Gonzalez, Malphurs, DelValle & Pickens, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, in their study of three-to six-month-old infants, Hossain et al (49) showed that infants of depressed mothers interacted better with their nondepressed fathers who could 'buffer' the effects of the mother's depression on infant interaction behaviour. In addition, a cross-sectional study (50) of 96 families with children between the ages of five and 10 years showed that in families in which the mother was depressed, children showed lower social and emotional competence if the father also had a psychiatric disorder.…”
Section: Role Of Fathersmentioning
confidence: 99%
“…Apesar de benéfico para o bebé, como consideram Hossain & et al (1994) e Hops & et al (1987, defendendo que em casos de depressão pós-parto o contacto com o pai não deprimido deverá ser promovido pois este desempenhará um efeito protector para o bebé, minimizando o impacto negativo da depressão da mãe, essa atitude não ajuda na recuperação materna uma vez que, nestes casos, a mãe tem tendência a sentir-se expropriada no seu papel maternal.…”
Section: Discussionunclassified
“…Segundo Brazelton & Cramer, (1992) quando o pai está presente serve de mediador da interacção da mãe com bebé, parecendo ter uma influência directa sobre o desenvolvimento da criança e exercendo um papel protector desse mesmo desenvolvimento (Hossain & et al, 1994;Hops & et.al., 1987). Hops, Biglan, Sherman, Arthur, Friedman, e Osteen (1987) mostraram que quando havia um bom relacionamento conjugal, os pais das famílias em que a mãe estava deprimida, tinham um maior envolvimento com as suas crianças, do que as próprias mães.…”
Section: El Comportamento Parental De Compañeros De Mujeres Con Depreunclassified